The feasibility of developing an embossed fiberglass filter media pack for air filtration devices / Goh Jenn Hsen - Goh, Jenn Hsen (2019)
As industrial technology continues to improve at an ever-increasing rate, this advancement comes at the expense of our environment, and more namely to the air quality. Consequently, the field of air filtration has garnered increasing attention and the demand for better air filtration devices has increased accordingly as well. An air filtration device is able to remove pollutants from an air stream. At the time of writing, the most commonly used air filtration medium is Fiberglass. Air filters with fiberglass medium has been commercially available since the 1990s and thus much development has been made to improve its performance. It is already known that pleating a Fiberglass media to form a media pack is able to decrease the air flow resistance of an air filter and increase the dust holding capacity of the air filter. To further improve on this, it was proposed to develop a filter media pack with an emboss design. This work aims to study the feasibility of developing such an air filter. With the aid of Computation Fluid Dynamic (CFD) simulations, the performance of a media pack with emboss design is predicted and found to have lower resistance to air flow and higher dust holding capacity as compared to an equivalent specification air filter. In addition, it was found that for a fiberglass media with 0.5mm thickness and 250 Pa air flow resistance at 0.53 cm/s air velocity, the optimum media pack dimensions are 120 mm Pleat Depth with Pleat Density of 6 Pleats Per Inch. Furthermore, cost analysis was performed to evaluate the Return of Investment of producing an air filter with embossed media pack. It was found that there is potential for high Return of Investment and thus it is feasible to develop an air filter with embossed fiberglass media pack.